“This is England”: Kano’s Made in the Manor and the Re-Writing of English Pop History - Ben WINSWORTH (E-REA)
This article considers Kano’s 2016 album Made in the Manor as a reflection on the ways in which grime challenged the white, Anglocentric tradition of post-war English pop and its narrow, exclusive representations of national identity. It looks at how Kano celebrates black music - both past and present - while self-consciously writing it into the popular cultural history of the UK as an evolving and powerful presence within the equally evolving nation.